Capital outflow in the countries exporting oil and gas as a deterrent to their economic development - Finogenova, Yulia; Domaschenko, Denis; Boyko, Olga; Krylov, Victor (Research Papers in Economics and Finance, 2016)
The economies of the countries exporting oil and gas generally have a positive balance of trade and a current account surplus. However, among them there are countries facing the problem of capital outflows under the financial account of the trade balance, which reduces financial resources for the economic growth and diversification. The main reasons for capital outflows lie in the specific features of the national law concerning foreign exchange as well as in the psychology of the behavior of the economic agents carrying out activities on the territory in question. The capital outflow is caused not only by a higher exposure of business operations, corruption, weak competitiveness of the economy etc. The authors have demonstrated that the most vulnerable countries exposed to the highest level of the capital outflow risk are the countries with hybrid exchange rate regimes, in contrast to the countries adopting hard exchange rate pegs or the floating exchange rate regime. The changes in the behavior of economic agents influencing the capital outflow during the transition of their currency exchange rate regimes to the floating regime have been studied on the example of Russia. Among the main parameters indicating excess capital outflows, the percentage of foreign currency denominated assets and liabilities in bank balance sheets has been chosen.In the long term the pattern of behavior of the economic agents in Russia will be similar to that of those in Norway and Canada, where even severe fluctuations of local currency exchange rates do not make money aggregates, the level of economy’s monetization and the percentage of foreign currency denominated assets and liabilities in bank balance sheets fluctuate significantly.